The mediating role of workplace relationship and communication satisfaction on the relationship between e-mail attitude and organisational commitment : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University (Albany) - Marchant, Lynette K (Massey University, 2000)
As an exploratory piece of research, this study investigated the use of e-mail by university staff and examined the relationship between e-mail attitude and organisational commitment. The mediating role on the attitude-commitment relationship by both satisfaction with overall communication and satisfaction with workplace relationships was also examined. A questionnaire was designed which incorporated Minsky and Marin's (1999) scale of Social and Nonsocial Uses of Electronic Messaging Systems, measures of satisfaction with the use of e-mail and with e-mail as a communication medium, Meyer and Allen's (1993) revised Organisational Commitment Scale, and subscales from Hill, Bahniuk and Dobos' (1989) Mentoring and Communication Support Scale and Furnham's (1996) Organisational Climate Questionnaire. A scale to measure e-mail attitude was developed specifically for this study using the tri-component model of attitude theory. The questionnaire was sent to all staff at Massey University's Albany and Palmerston North campuses (N = 2253). Of the number sent, 575 were returned, with a proportional representation from the two campuses and the five colleges of the university. Use of e-mail was found to be predominantly used for task related purposes, with administration being the most commonly reported function that e-mail was used for. Factor analysis demonstrated three underlying components, affective, behavioural and cognitive, of the E-mail Attitude Scale. A series of hierarchical multiple regressions as outlined by Baron and Kenny (1986) were conducted to explore the potential mediating effects of both communication satisfaction and workplace relationship satisfaction. Communication satisfaction completely mediated the relationship between affective attitudinal component and both normative and affective organisation commitment. In turn, the satisfaction with workplace relationship variables partially mediated the relationship between the affective attitude component and affective commitment, with only collegial social support partially mediating the relationship between affective e-mail attitude and normative commitment. The results are discussed in relation to relevant demographic variables. Limitations and potential directions for future research are also highlighted.
Keywords: Electronic mail messages; Communication in organizations; Organisational behavior